Investigation of Deformational Processes in Tbilisi Underground Earth-Tidal Laboratory - Kartvelishvili, Karlo Z. (Journals of Georgian Geophysical Society, 2017)
The results of extensometer observations carried out to study the tidal phenomena in the Earth solid body can also be used for measuring slow and seismic deformations of the Earth’s crust. In order to observe the secular, tidal, meteorological, and seismic deformations of the Earth’s surface, a three-component quartz extensometer has been set in the Tbilisi Underground Tidal Laboratory of the Institute of Geophysics of the Academy of Sciences of Georgia. In 1963-1976, horizontal extensometer used photo-optical transducers. Since 1976 all components (horizontal and vertical) use capacitive transducers KD-2. The component N66°5E with a 42 m base has the sensitivity of 0.22ˑ10¯¹⁰mm¯¹. The component N30°W having the base of 14.5 m records with the sensitivity 0.70ˑ10¯¹⁰mm¯¹and third vertical component with a base 6.45 m have sensitivity (0.57-1.75)ˑ10¯¹⁰mm¯¹ for different periods of observations. The results of extensometer observations are given.